Processing pathways of Cu2Zn(SnGe)Se4 based solar cells: The role of CdS buffer layer. (15th August 2017) - Vigil-Galán, O.; Courel, Maykel; Andrade-Arvizu, J.A.; Sánchez, Y.; Espíndola-Rodríguez, M.; Saucedo, E.; Seuret-Jiménez, D.; González, R.
Abstract: One important issue concerning kesterite solar cell technology is CdS/kesterite interface. As a result, routes to promote kesterite solar cell efficiency should be mainly focused on improving CdS/kesterite interface quality. In this work, results on a comparative study of Cu2 Zn(SnGe)Se4 solar cells processed with different CdS buffer layers deposited by chemical bath deposition technique are presented. Different sources of Cd such as cadmium chloride, cadmium nitrate and cadmium sulfate are considered for CdS fabrication. The influence of these CdS buffer layers on the properties of the solar cells is discussed. It is demonstrated that CdS buffer layers obtained from cadmium chloride and cadmium nitrate could be more adequate choices for solar cell fabrication. Enhanced solar cell properties are obtained as a result of an improvement of the heterojunction properties. A complete characterization of devices is presented.